Enhancing motivation and psychological wellbeing in the workplace through conscious physical activity: Suggestions from a qualitative study examining workers' experience - Signorini, Gabriele; Scurati, Raffaele; D'Angelo, Chiara; Rigon, Marta; Invernizzi, Pietro Luigi (Frontiers in Psychology, 2022)
After major COVID-19 restrictions, hybrid solutions combining smart working and work in presence were set. In particular, to meet the employees' needs and well-being, the working environment is a component highly affecting the workers’ life. Based on a socio-ecological and multilevel methodology, the UP150 concept (Proactive Office 150) represents a possible innovative solution to satisfy the employee’s needs and valorize flexible work. It promotes physical activity and active pauses during the usual workflow by inserting elements such as specific architectural changes, a dedicated App and physical activity professional figures as the wellness coaches. The present study is the last step of the preliminary actions planned to check the benefits of the UP150 concept and aims to explore the workers’ perceptions after experiencing such a project. The qualitative analysis of a preliminary survey (concerning information about the company structure and workers’ habits) performed before conducting a randomized controlled trial intervention study and the analysis of the semi-structured interviews after eight weeks of a UP150 experience served as datasets for this study, and have been examined and discussed. In the preliminary survey, the prevalently young (under 40) and generally active (57%) workers declared to be motivated to exercise but hindered in physical exercising because of lack of time and excessive workload. After eight weeks of work at a modified workplace designed beneath the UP150 rationale, the workers displayed noticeable positive perceptions and appreciation. The qualitative analysis confirmed and supported the effectiveness of the UP150 concept that previous research already found in quantitative parameters related to employees’ motor efficiency, psychophysical status, and the amount of physical activity. Participants reported beneficial perceived effects on their wellness and psychophysical status following a UP150 concept experience. Moreover, the concept improved social relationships and increased motivation. In conclusion, the UP150 concept efficiently promoted a positive perception of physical exercise and addressed the employees toward the assumption of healthy behaviors fitting the physical literacy paradigm.